2007
DOI: 10.1063/1.2800339
|View full text |Cite
|
Sign up to set email alerts
|

Onset of convection in two liquid layers with phase change

Abstract: We perform linear stability calculations for horizontal fluid bilayers that can undergo a phase transformation, taking into account both buoyancy effects and thermocapillary effects in the presence of a vertical temperature gradient. We compare the familiar case of the stability of two immiscible fluids in a bilayer geometry with the less-studied case that the two fluids represent different phases of a single-component material, e.g., the water-steam system. The two cases differ in their interfacial boundary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…In this paper we reconsider this instability, including the effects of buoyancy and surface tension gradients, and assume that the interface remains at local thermodynamic equilibrium. This extends our previous calculations for the watersteam system, 8 which were performed at temperatures close to the thermodynamic critical point where the densities of the two phases are comparable. In contrast to that work, which did not find any instabilities for cooling from below, we find in the present study that the oscillatory instability found by Huang and Joseph occurs if there is a large difference in the densities of the two fluids.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this paper we reconsider this instability, including the effects of buoyancy and surface tension gradients, and assume that the interface remains at local thermodynamic equilibrium. This extends our previous calculations for the watersteam system, 8 which were performed at temperatures close to the thermodynamic critical point where the densities of the two phases are comparable. In contrast to that work, which did not find any instabilities for cooling from below, we find in the present study that the oscillatory instability found by Huang and Joseph occurs if there is a large difference in the densities of the two fluids.…”
Section: Introductionmentioning
confidence: 88%
“…For a hundred-fold increase in ‫ء‬ , the critical values of both G and a change by two orders of magnitude; the critical values of i do not change significantly. The large increase in the critical values of G as the densities of the two phases becomes comparable probably accounts for the absence of this mode in our previous calculations,8 where ‫ء‬ = 0.368.…”
mentioning
confidence: 85%
“…(16) reduces to the condition of local thermodynamic equilibrium, used in several phase-boundary problems. 8,10,11,25 Therefore, Eq. (16) is an intermediate relation connecting the two different interfacial conditions appearing in the studies of two-phase systems with phase change.…”
Section: B Boundary Conditionsmentioning
confidence: 99%
“…The full linear stability analyses of this system were performed in several papers. 7,8,9,10,11 Despite the apparent simplicity of the configuration, this system includes a free surface and interfacial boundary conditions involving phase change, and therefore is very sophisticated. In order to simplify this problem, we apply long-wave approximation to both layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation